2023
DOI: 10.1094/pdis-05-22-1092-re
|View full text |Cite
|
Sign up to set email alerts
|

A LAMP-Based Toolbox Developed for Detecting the Major Pathogens Affecting the Production and Quality of the Chinese Medicinal Crop Aconitum carmichaelii

Abstract: Aconitum carmichaelii Debeaux is a traditional Chinese medicinal herb that has been utilized for approximately two thousand years. However, as cultivation has increased, there have been more reports of A. carmichaelii infections caused by four major pathogenic fungal species, Fusarium oxysporum, F. solani, Mucor circinelloides, and Sclerotium rolfsii, resulting in increased disease incidences and limited production and quality. To detect these infections, we developed a LAMP-based toolbox in this study. The cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Due to the mineral oil overlay, LAMP-amplified products were not recovered for further testing, and electrophoresis was not performed. Furthermore, many researchers have reported that colour change results were consistent with electrophoresis results [42,43]. Therefore, LAMP is an alternative nucleotide amplification method that is rapid, simple, highly sensitive, and suitable for analysing pathogens in the field.…”
Section: Discussionmentioning
confidence: 76%
“…Due to the mineral oil overlay, LAMP-amplified products were not recovered for further testing, and electrophoresis was not performed. Furthermore, many researchers have reported that colour change results were consistent with electrophoresis results [42,43]. Therefore, LAMP is an alternative nucleotide amplification method that is rapid, simple, highly sensitive, and suitable for analysing pathogens in the field.…”
Section: Discussionmentioning
confidence: 76%
“…Among these regions, the longest period of A. carmichaelii cultivation dates back more than a thousand years in Jiangyou City, Sichuan Province. Since 2015, A. carmichaelii cultivation has expanded to approximately 3000 hectares in Shaanxi and Sichuan Provinces, establishing it as a significant local industry [5]. A. carmichaelii plants are cultivated through seed and by vegetative propagation from lateral roots.…”
Section: Introductionmentioning
confidence: 99%